Increased Menopausal Age Reduces the Risk of Parkinson's Disease: A Mendelian Randomization Approach. Issue 10 (23rd August 2021) - Kusters, Cynthia D.J.; Paul, Kimberly C.; Duarte Folle, Aline; Keener, Adrienne M.; Bronstein, Jeff M.; Bertram, Lars; Hansen, Johnni; Horvath, Steve; Sinsheimer, Janet S.; Lill, Christina M.; Ritz, Beate R.
ABSTRACT: Background: Studies of Parkinson's disease (PD) and the association with age at menarche or menopause have reported inconsistent findings. Mendelian randomization (MR) may address measurement errors because of difficulties accurately reporting the age these life events occur. Objective: We used MR to assess the association between age at menopause and age at menarche with PD risk. Methods: We performed inverse variant‐weighted (IVW) MR analysis using external genome‐wide association study (GWAS) summary data from the United Kingdom biobank, and the effect estimates between genetic variants and PD among two population‐based studies (Parkinson's disease in Denmark (PASIDA) study, Denmark, and Parkinson's Environment and Gene study [PEG], United States) that enrolled 1737 female and 2430 male subjects of European ancestry. We, then, replicated our findings for age at menopause using summary statistics from the PD consortium (19 773 women), followed by a meta‐analysis combining all summary statistics. Results: For each year increase in age at menopause, the risk for PD decreased (odds ration [OR], 0.84; 95% confidence interval [CI], 0.73–0.98; P = 0.03) among women in our study, whereas there was no association among men (OR, 0.98; 95% CI, 0.85–1.11; P = 0.71). A replication using summary statistics from the PD consortium estimated an OR of 0.94 (95% CI, 0.90–0.99; P = 0.01), and we calculated a meta‐analytic OR of 0.93 (95% CI, 0.89–0.98; P = 0.003). There was no indication for an association between age at menarche and PD (OR, 0.75; 95% CI, 0.44–1.29; P = 0.29). Conclusions: A later age at menopause was associated with a decreased risk of PD in women, supporting the hypothesis that sex hormones or other factors related to late menopause may be neuroprotective in PD. © 2021 International Parkinson and Movement Disorder Society